PEMBERDAYAAN MASYARAKAT DI DESA TITIDU MELALUI LITERASI RUMAH ABC (ASYIK BACA DAN CERITA) - Ahmad Sugeng Riady (Turast: Jurnal Penelitian dan Pengabdian, 2021)
This article discusses literacy in Titidu Village through the Rumah ABC (Fun to Read and Story) program. The reading room in Titidu Village as a place for literacy already exists, but the interest in books and the empowerment of the reading room has not been maximized. In addition, the reading room space in the hall must share space with other items and activities. So that the opening and closing hours of the reading room are not fixed. As a result, the reading room is rarely visited by the public, especially children. This article was created with the aim of providing an overview of literacy in Titidu Village through the ABC House (Fun to Read and Stories). The methods used are observation and interviews. Observations include direct observation of the reading room of the Titidu Village hall. While the interviews included village officials and children who were both objects and actors in the ABC House (Fun to Read and Stories). In this article, it was found that the ABC House (Fun to Read and Stories) could foster children's literacy interest in Titidu Village. This is indicated by an increase in the number of children participating in the ABC House program (Fun to Read and Stories). In addition, the number of books that children read every meeting is increasing. This ABC (Fun to Read and Story) house also serves to provide protection for children through literacy.